2012 IEEE International Symposium on Alternative Energies and Energy Quality (SIFAE) 2012
DOI: 10.1109/sifae.2012.6478898
|View full text |Cite
|
Sign up to set email alerts
|

Illumination benefits using LED high brightness bulb compare to traditional illumination systems

Abstract: In this article, a new kind of led emitter diode is used. The HB-LED (High Brightness Light Emitter Diode), were selected and tested and the results compared with existing light sources used in the Universidad Autónoma de Occidente. Results shows better visual perception of space and great energy savings between 41% and 73% of power consumption compared with actual technology such as high pressure sodium bulbs and energy saving light bulb. The usage of HB-LED reduce the cost of solar systems used as power sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…This LED technology has increasingly been used in many electric devices, and one of their great advantages over other light sources is the low battery consumption (Macias et al 2012). Light-emitting diodes have been implemented in various traps to produce a more efficient lighting system that reduces power consumption by 50-60% (Cohnstaedt et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This LED technology has increasingly been used in many electric devices, and one of their great advantages over other light sources is the low battery consumption (Macias et al 2012). Light-emitting diodes have been implemented in various traps to produce a more efficient lighting system that reduces power consumption by 50-60% (Cohnstaedt et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el ángulo de emisión de luz es menor a 180 grados, toda la luz generada está enfocada hacia la parte frontal del LED. [12].…”
Section: Diodo Emisor De Luz (Led)unclassified
“…The establishment of LEDs instead of traditional artificial lighting systems results in energy saving. For instance, while comparing LEDs with traditional lighting systems, Macias et al [12] reported that there was a great energy saving, between 41% and 73% of power consumption, compared with the technology of that period such as HPS lamps. Similarly, Serrano-Tierz [13] concluded that the replacement of metal halide lights by LEDs luminaries resulted in a high energy saving and an increase of the life span of the luminaires.…”
Section: Introductionmentioning
confidence: 99%